Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = 19x2 - 11x3 + 9 - 20x
= -11x3 + 19x2 - 20x + 9
B = 1 + x2 - 4x
= x2 - 4x + 1
-11x 3 +19x 2 -20x + 9 x 2 -4x+1 -11x -11x 3 +44x -25x -9x + 9 2 2 -25 -25x 2 +100x-25 -109x+36 vậy Q = -11x - 25 và R = -109x + 36 -11x
a) \(\left(2x-1\right)^2-\left(x+2\right)^2-3x^2+5x\)
\(=4x^2-4x+1-\left(x^2+4x+4\right)-3x^2+5x\)
\(=x^2-3x-3\)
b) \(\left(x+2\right)\left(x-1\right)+2\left(3x-2\right)^2+4x-19x^2\)
\(=x^2+2x-x-2+2\left(9x^2-12x+4\right)+4x-19x^2\)
\(=x^2+2x-x-2+18x^2-24x+8+4x-19x^2\)
\(=-19x+6\)
c) \(2\left(3-x\right)\left(x-2\right)-\left(3x+1\right)^2+5x-11x^2\)
\(=6-2x\left(x-2\right)-\left(9x^2+6x+1\right)+5x-11x^2\)
\(=6-2x^3+4x-9x^2-6x-1+5x-11x^2\)
\(=-2x^3-20x^2+3x+5\)